العلاقة بين منحنيات الشدة المطرية الأعظمية في محطة طرطوس - حماد منذر علي; حسين ديما حسن (Latakia University Journal -Engineering Sciences Series, 2019)
The research area is located in Tartous Governorate, where the Tartous station was launched due to the availability of rainfall values of 15min-30min-1h-3h-6h-24h for a period of 34 years. The research aims at finding a relationship between the maximum rainfall intensity for any duration and frequency with the reference rain intensity by conducting a statistical and analytical study of the rainfall data using the Minitab program, which helps in completing the data that is not available and also finding suitable relationships for areas where measurements are not available by drawing contour lines using the GIS program using two methods, the traditional method and the simple measurement method The study identified two relationships, the first using the traditional method and the error of 8.9% and the second method of simple measurement and error of 1.9%. We recommend to generalization of research methodology on the rest of the stations deployed in the country. تقع منطقة البحث في محافظة طرطوس حيث تم الانطلاق بالدراسة من محطة طرطوس وذلك بسبب توافر قيم الهطولات المطرية للمدد15 min -30min-1h-3h-6h-24h لفترة زمنية تمتد على 34 سنة. يهدف البحث إلى إيجاد علاقة تربط بين الشدة المطرية الأعظمية لأي مدة وتكرار مع الشدة المطرية المرجعية عن طريق إجراء دراسة إحصائية وتحليلية لبيانات الهطول المطري باستخدام برنامجMinitab، مما يساعد في استكمال البيانات الناقصة وأيضاً إيجاد علاقات ملائمة للمناطق التي لا تتوفر فيها قياسات برسم خطوط التساوي للبارامترات باستخدام برنامج GIS ، وذلك من خلال المقارنة بين طريقتين هما الطريقة التقليدية وطريقة القياس البسيط، وحساب قيمة الخطأ لكل منهما واختيار الطريقة الأكثر ملائمة لسلسلة البيانات. توصلت الدراسة إلى تحديد علاقتين أولهما باستخدام الطريقة التقليدية وبخطأ قدره 8.9%، والثانية بطريقة القياس البسيط وبخطأ قدره 1.9%، ونوصي بتعميم منهجية البحث على باقي المحطات المنتشرة في القطر.